Marburg virus disease: the paradox of Nigeria’s preparedness and priority effects in co-epidemics - Reuben, Rine Christopher (2023)
The recent outbreaks of Marburg virus disease (MVD) in Guinea and Ghana have become a major public health concern not only to the West African sub-region but a threat to global health.